2021
DOI: 10.3233/bmr-200109
|View full text |Cite
|
Sign up to set email alerts
|

Comparing durability of water- and land-based exercise benefits among older adults in South Korea: A randomized controlled trial with 1-year follow-up

Abstract: BACKGROUND: Aquatic exercise can improve strength, flexibility, and aerobic function while safely providing partial weight-bearing support through viscosity and buoyancy. OBJECTIVE: The aim of the present study was to compare the effects of water-based exercise with land-based exercise before and after a 10-week exercise intervention and again at one-year follow-up. METHODS: Eighty participants aged 65 years and older were randomly assigned to either a water- or a land-based 10-week exercise program. Assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Moreover, both groups maintained their lower body strength values six months after the intervention period. In contrast, Oh and Lee [33] reported more profound increases in hip, knee, and hand-grip measures in the WBE group, during different testing points, whereas comparable improvements were shown during the chair-stand and the arm-curl test. The WBE group of Oh et al's study [27] reported significantly lower body muscle strength improvements (hip abduction and adduction), but no differences between the two groups were observed for the hip flexion and extension values.…”
Section: Muscle Strengthmentioning
confidence: 72%
See 4 more Smart Citations
“…Moreover, both groups maintained their lower body strength values six months after the intervention period. In contrast, Oh and Lee [33] reported more profound increases in hip, knee, and hand-grip measures in the WBE group, during different testing points, whereas comparable improvements were shown during the chair-stand and the arm-curl test. The WBE group of Oh et al's study [27] reported significantly lower body muscle strength improvements (hip abduction and adduction), but no differences between the two groups were observed for the hip flexion and extension values.…”
Section: Muscle Strengthmentioning
confidence: 72%
“…Only in three cases [24,25,33] a comprehensive analysis of the physical fitness profile was performed. In the rest of the studies, the measure of cardiorespiratory fitness was absent, while two high-quality studies focused on a single parameter, namely aerobic endurance [32] and body composition [31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations